Gobierno electrónico como herramienta del Gobierno Autónomo Descentralizado Intercultural del Cantón Pujilí. - Allauca Lidioma, Margarita Del Carmen (2023)
The Intercultural Decentralized Autonomous Government of the Pujilí Canton, manually executes the attention of all the services required by citizens, as well as the internal processes of the administration and other public information generated by the different directorates of the institution, which implies that the activities inherent of attention and service to citizens become limiting and do not allow their effectiveness in public administration. For this reason, the objectives of this research were: to establish the theoretical and conceptual bases on electric government in the Municipal GADS, to diagnose the current situation of electronic government management in the GADMI of the Pujilí Canton, and to propose a strategy to improve the management of electronic Government in the GADMI of the Pujilí canton. For this, a descriptive quantitative research was used, a survey was carried out aimed at a sample of the population that pays property taxes in the canton. Once the results of the situational diagnosis were obtained, it was found that more than 50% of the population agrees with the development of a computer system that would allow them to carry out their management more easily and quickly. In this sense, a proposal was presented based on the development of a citizen service portal as an electronic government tool, whose main objective is to improve the interaction between the government and citizens, offering easy and convenient access to government services, information and attendance. This platform seeks to streamline procedures, facilitate consultations and encourage citizen participation.